Effect of the Juntos social program on female labor supply in Peru - García, Luis (2017)
Over the last ten years, the Peruvian conditional transfer program, Juntos, has expanded significantly. The objective of this program is to promote school attendance, reduce child labor, and monitor the growth and development of children in impoverished areas. Although improvements in these indicators have been appreciated, there may be unforeseen impacts on the households receiving the transfers. In this study, we focus on the program’s impact on the working hours of women in recipient households. According to the standard theory (Becker, 1965), transfers could reduce the labor supply by assuming leisure to be a normal good. According to theories of family economics, transfers to one member can affect the allocation of resources to all members of the household (Chiappori, 1992). The international empirical literature is inconclusive, pointing to non-existent, negative, and even positive effects (Alzúa, Cruces and Ripani, 2012; Gassman and Trindade, 2016). In the Peruvian case, the most similar study is that of Fernández and Saldarriaga (2014), who study the impact of the closeness of the program payment date on female labor supply, finding a negative effect during the week of payment. Our study goes further, in that: (i) we consider that transfers could result in a reallocation of resources within the household; (ii) we quantify the changes in working hours from one year to the next as a result of the program; (iii) in the light of structural econometric models, we control the main biases (unobservable heterogeneity, selection bias, and endogeneity), since it is not possible to apply an experimental design. Using the panel component of Peru’s National Household Survey (Encuesta Nacional de Hogares del Perú), we find that the Juntos program reduces the paid work of women in beneficiary households by nine hours per week. En los últimos diez años, el Perú ha experimentado una importante expansión del programa de transferencias condicionadas Juntos. El objetivo de este programa es incentivar la asistencia escolar, reducir el trabajo infantil y seguir el crecimiento y desarrollo de los niños en zonas de pobreza. Se han observado mejoras en estos indicadores; sin embargo, pueden existir impactos no previstos en el hogar que recibe la transferencia. Este estudio se enfoca en el impacto sobre las horas de trabajo de las mujeres de hogares beneficiarios.  Según la teoría estándar (Becker, 1965), las transferencias pueden reducir la oferta laboral asumiendo al ocio como un bien normal. Según las teorías de la economía familiar, las transferencias a un miembro pueden afectar la asignación de recursos de todos los miembros dentro del hogar (Chiappori, 1992). La literatura empírica internacional no es concluyente, mostrando efectos nulos, negativos o inclusive positivos (Alzúa, Cruces y Ripani, 2012; Gassman y Trindade, 2016). En el caso peruano, el estudio más cercano es el de Fernández y Saldarriaga (2014), quienes estudian el impacto de la proximidad de la fecha de pago del programa Juntos en la oferta laboral femenina, encontrando un efecto negativo. Nuestro estudio va más allá porque: (i) considera que las transferencias pueden ocasionar una reasignación de los recursos dentro del hogar; (ii) cuantifica los cambios en las horas de trabajo de un año a otro como consecuencia del programa; (iii) a la luz de modelos econométricos estructurales, controlamos los principales sesgos (heterogeneidad inobservable, sesgo de selección y endogeneidad), dado que no se puede aplicar un diseño experimental. Utilizando la Encuesta Nacionales de Hogares Panel del Perú de 2011-2013, encontramos que el programa Juntos reduce 9 horas semanales el trabajo remunerado de las mujeres de hogares beneficiarios.